2022
DOI: 10.1111/dom.14866
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional association of metrics derived from continuous glucose monitoring with cognitive performance in older adults with type 2 diabetes

Abstract: Aim To examine the association between continuous glucose monitoring (CGM)‐derived metrics and cognitive performance in older adults with type 2 diabetes (T2D). Materials and methods A total of 100 outpatients with T2D aged 70 years or older were analysed. Participants underwent CGM for 14 days. As CGM‐derived metrics, mean sensor glucose (SG), glucose coefficient of variation (CV), time in range (TIR; 70‐180 mg/dl), time above range (TAR; > 180 mg/dl) and time below range (TBR; < 70 mg/dl), were calculated. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(33 citation statements)
references
References 31 publications
(59 reference statements)
4
28
1
Order By: Relevance
“…Some studies have shown that TIR is closely related to cognitive dysfunction [8,22]. Contrary to a previous study, we did not observe a relationship between TIR and global cognition or speci c cognitive domains.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Some studies have shown that TIR is closely related to cognitive dysfunction [8,22]. Contrary to a previous study, we did not observe a relationship between TIR and global cognition or speci c cognitive domains.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, it is recommended that the glycemic control target value should be relaxed for T2DM patients with cognitive impairment. One study demonstrated that a higher TAR > 10.0 mmol/L was associated with a lower performance in executive functioning and working memory [22]. Our results are in line with the study discussed above.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the COVID-19 pandemic affected recruitment and assessment, and as described in the previous study, 9 Of 100 participants, we included those who completed the MoCA-J at baseline and 1-year follow-up, which was performed from February 2022 to February 2023.…”
Section: Umin000042181mentioning
confidence: 99%
“…Significant cross-sectional associations were observed between hyperglycaemia/hypoglycaemia and poor cognitive performance and between a high TIR and a better cognitive performance. [9][10][11] However, their longitudinal relationships remained unclear.…”
Section: Introductionmentioning
confidence: 99%